Analysis of Internal Friction Angle and Cohesion Value for Road Base Materials in a Specified Gradation - Grawira Ganjur Giwangkara; Azman Mohamed; Hasanan Md. Nor; Nur Hafizah A.; Rachmat Mudiyono (Universitas Islam Sultan Agung, 2020)
Internal friction angle (φ) is one of the important parameter in a foundation engineering, especially in the stress distribution event. The higher value of the internal friction angle shows the higher of the material can withstand the lateral force. Cohesion factor (c) is also an integral part of the shear strength for the foundation material. In the granular soil such as sand or non-cohesive material, including aggregate, cohesion value usually assumed as zero, although some cohesion factor may be applied. In this research, two different materials were tested for their shear strength. The materials were Natural Crushed Aggregate (NCA) and Recycled Concrete Aggregate (RCA). Each material was also tested under two different circumstances. First, the materials were tested in a small-scale direct shear (SSDS) test with the maximum material size of 0.425 mm and 2.0 mm. Secondly, the materials were tested in a large-scale direct shear (LSDS) test with the graded size of aggregate according to road base layer specification. The SSDS showed the internal friction angle of NCA and RCA varies from 26.20 to 29.82 degrees. Whereas the LSDS showed the internal friction angle of NCA and RCA are 44.90 and 29.16 respectively. Both of SSDS and LSDS also showed the cohesion value of NCA and RCA.